2(v-5)-4=-5(-4v+1)-6v

Simple and best practice solution for 2(v-5)-4=-5(-4v+1)-6v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(v-5)-4=-5(-4v+1)-6v equation:


Simplifying
2(v + -5) + -4 = -5(-4v + 1) + -6v

Reorder the terms:
2(-5 + v) + -4 = -5(-4v + 1) + -6v
(-5 * 2 + v * 2) + -4 = -5(-4v + 1) + -6v
(-10 + 2v) + -4 = -5(-4v + 1) + -6v

Reorder the terms:
-10 + -4 + 2v = -5(-4v + 1) + -6v

Combine like terms: -10 + -4 = -14
-14 + 2v = -5(-4v + 1) + -6v

Reorder the terms:
-14 + 2v = -5(1 + -4v) + -6v
-14 + 2v = (1 * -5 + -4v * -5) + -6v
-14 + 2v = (-5 + 20v) + -6v

Combine like terms: 20v + -6v = 14v
-14 + 2v = -5 + 14v

Solving
-14 + 2v = -5 + 14v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-14v' to each side of the equation.
-14 + 2v + -14v = -5 + 14v + -14v

Combine like terms: 2v + -14v = -12v
-14 + -12v = -5 + 14v + -14v

Combine like terms: 14v + -14v = 0
-14 + -12v = -5 + 0
-14 + -12v = -5

Add '14' to each side of the equation.
-14 + 14 + -12v = -5 + 14

Combine like terms: -14 + 14 = 0
0 + -12v = -5 + 14
-12v = -5 + 14

Combine like terms: -5 + 14 = 9
-12v = 9

Divide each side by '-12'.
v = -0.75

Simplifying
v = -0.75

See similar equations:

| n+25=24 | | -2x-5y=-11 | | 5x=11x-4 | | 1-6(2-x)-29x=x | | 4u-2=-22 | | -9x+y=71 | | 2a-7=19 | | 6x^3-54x^2+84=6x(x-2)(x+7) | | 2300=58x | | 2450=23x | | 2450=23 | | 3x+2-7=9x+16 | | 2450=58x | | 11+7=260 | | 2450=58 | | m-48=-39 | | 22-6x=7 | | m^2-4m-11=0 | | -24-53=39-5 | | (7x^4+5x^3)+(7x^4-4x^3-6x)=0 | | 3[x-4]=-27 | | 4y+3y+7y+y= | | tc+sc-td-sd= | | -30+5k=-8(k+7) | | 2200=56x | | (a+2b)+3c=a+(2b+3c) | | -4x-3y=-5 | | 7b-5=2(2b-13) | | -7[x-3]=-14 | | -39-8p=3-6(p+7) | | 2t^3-6t^2+12=0 | | x+9+4x=16-5 |

Equations solver categories